A New Method of Measuring Impedance Cardiography for Cardiac Output Estimation by Directly Digitizing the High Frequency Modulated Signal at Lower Sampling Rate - Dao, Viet Hung; Phan, Dang Hung; Dinh, Thi Nhung; Vu, Duy Hai; Chu, Quang Dan (Old Journal, 2018)
Cardiac output (CO) is an important hemodynamic index to assess the heart condition of the patients. Impedance cardiography (ICG) is an advanced method that can noninvasively and continuously monitor CO based on the variation of thorax impedance. Since the variation is very small compared to the base impedance, the acquisition solutions generally require complicated analog processing circuits. This makes the output influenced by external noise, temperature, and component tolerances. This study presents a new method of measuring the changes in bioimpedance with high reliability by directly digitizing the modulated thoracic impedance signal. The proposed method has a notable advantage that allows to be implemented with low-performance hardware. The experimental results showed that the extracted data is not only similar to the reference one, but also stable over long working time. The early digitization solution makes the processing steps could be highly flexible and easy to be upgraded in further research.